Brain injury, endocrine disruption, and immune dysregulation in HIV-positive men who have sex with men with late HIV diagnosis - He, Yihui; Liu, Hao; Ren, Meixin; Sun, Gaungqiang; Ma, Yundong; Cai, Miaotian; Wang, Rui; Wang, Lei; Zhang, Tong; Zhang, Yang (Frontiers in Immunology, 2025)
BackgroundIn the realm of public health, late human immunodeficiency virus (HIV) diagnosis remains prevalent and is associated with neuropsychiatric adverse events. However, there is limited documentation regarding the impact of late HIV diagnosis (LD) on brain integrity, neurotrophic factors, endocrine function, and immunity in HIV-positive men who have sex with men (MSM).MethodsParticipants (38 LD and 34 non-LD of MSM) underwent comprehensive infectious disease and psychiatric assessments, multimodal magnetic resonance imaging (MRI) scans, neurotrophic factors, endocrine, and immunological evaluations. Immune cell levels, along with peripheral plasma concentrations of neurotrophic factors and hormones, were measured using enzyme-linked immunosorbent assays and flow cytometry, respectively. T1-weighted images along with resting-state functional MRI were applied to assess brain function and structure while also examining correlations between imaging alterations and clinical as well as peripheral blood variables. The data for this study originated from a subset of the cohort in HIV-associated neuropsychiatric disorders research.ResultsCompared to participants in the non-LD group, those in the LD group showed a lower total gray matter volume (GMV), with reduced GMV primarily observed in the left supramarginal gyrus. Participants in the LD group exhibited differences in brain function with certain regions and decreased functional connectivity between these altered regions and connected structures. A two-way factorial analysis of variance examining the main effects and interactions between groups and neuropsychiatric disorders revealed significant main effects of LD on specific brain regions. Furthermore, we found that individuals in the LD group had higher levels of cortisol, a lower frequency of central memory T cells, and elevated expression levels of perforin in double-negative T cells. These imaging findings were significantly correlated with endocrine, immune, and clinical variables.ConclusionThis study suggests that LD may contribute to brain injury, endocrine disruption, and immune dysregulation in HIV-positive MSM. Consequently, there is an urgent need to develop public health strategies targeting late diagnosis, with a focus on strengthening screening and early detection for high-risk populations, as well as monitoring brain injury, endocrine, and immune functions in individuals with LD, and formulating precise, individualized intervention strategies to reduce the long-term impact of LD on the health of HIV-positive MSM.